Umbilical Cord Mesenchymal Stromal Cells for Cartilage Regeneration Applications. (6th January 2022) - Russo, E.; Caprnda, M.; Kruzliak, P.; Conaldi, P. G.; Borlongan, C. V.; La Rocca, G.
Abstract : Chondropathies are increasing worldwide, but effective treatments are currently lacking. Mesenchymal stromal cell (MSCs) transplantation represents a promising approach to counteract the degenerative and inflammatory environment characterizing those pathologies, such as osteoarthritis (OA) and rheumatoid arthritis (RA). Umbilical cord- (UC-) MSCs gained increasing interest due to their multilineage differentiation potential, immunomodulatory, and anti-inflammatory properties as well as higher proliferation rates, abundant supply along with no risks for the donor compared to adult MSCs. In addition, UC-MSCs are physiologically adapted to survive in an ischemic and nutrient-poor environment as well as to produce an extracellular matrix (ECM) similar to that of the cartilage. All these characteristics make UC-MSCs a pivotal source for a stem cell-based treatment of chondropathies. In this review, the regenerative potential of UC-MSCs for the treatment of cartilage diseases will be discussed focusing on in vitro, in vivo, and clinical studies.